2020
DOI: 10.21203/rs.3.rs-35676/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Impact of COVID-19 on Gastric Cancer Surgery: A Single-Center Retrospective Study

Abstract: Background: The coronavirus disease 2019 (COVID-19) has been declared a global pandemic by the World Health Organization. Patients with cancer are more likely to incur poor clinical outcomes. Due to the prevailing pandemic, we propose some surgical strategies for gastric cancer patients. Methods: The ‘COVID-19’ period was defined as occurring between 2020-01-20 and 2020-03-20. The enrolled patients were divided into two groups, pre-COVID-19 group (PCG) and COVID-19 group (CG). A total of 109 patients with gast… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 2 publications
1
9
0
Order By: Relevance
“…The whole world still seeks an answer to whether the COVID-19 pandemic will be over, or people will get used to living with it. Gastric cancer surgeries have been decreased in a given time period from a total number of 81 to 63 at our hospital, the same reduction was detected by several centers [ 5 ]. Although the difference was not significant, the emergency gastric cancer surgery rate increased during the pandemia period (increased from 15 to 23%).…”
Section: Discussionsupporting
confidence: 71%
“…The whole world still seeks an answer to whether the COVID-19 pandemic will be over, or people will get used to living with it. Gastric cancer surgeries have been decreased in a given time period from a total number of 81 to 63 at our hospital, the same reduction was detected by several centers [ 5 ]. Although the difference was not significant, the emergency gastric cancer surgery rate increased during the pandemia period (increased from 15 to 23%).…”
Section: Discussionsupporting
confidence: 71%
“…Li et al [17] found that the time of surgery and estimated blood loss were the same before and after the pandemic. Our study observed prolonged surgeries and lower amounts of blood loss in the COVID-19 group.…”
Section: Discussionmentioning
confidence: 98%
“…The retrospective study by Li et al [17] examining the effects of the COVID-19 pandemic on gastric cancer treatment reported that the COVID-19 cost per patient was higher, which was attributed to the prolonged hospital stay. Our study also established increased cost per patient during COVID-19 period.…”
Section: Discussionmentioning
confidence: 99%
“…The disruption is lower as compared to other nationwide studies that reported up to 50% decrease in the number of major cancer surgeries. [30][31][32][33] This re ects the mitigation strategies adopted by the cancer care specialists in the form of segregation of Covid care and adopting best practice guidelines for cancer treatment during the pandemic as prescribed by Indian Association of Surgical Oncology (IASO) COVID-19 guidelines and the Tata Memorial Centre COVID-19 working group and redesignate oncological surgeries as essential rather than elective. [14,[34][35][36] This study highlighted the maximum disruption in esophagogastric and hepatopancreatic cancer surgeries ranging from 25-33%.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the centres in Japan reported 50% decrease in the number of gastrectomies performed in the active Covid phase. [31] The disruption of optimal management of upper gastrointestinal cancers has been uniformly reported across the countries as the endoscopic services were largely discontinued in the early part of the Covid-19 as they were considered as high aerosol generating procedures. This disruption was further potentiated by the fact that alternative treatment options like chemo radiotherapy were substituted for surgically resectable diseases.…”
Section: Discussionmentioning
confidence: 99%